Perancangan Desain Karakter Buku Ilustrasi Berbasis Augmented Reality Astronomi Khusus Anak Tunarungu - Giana Fatimah Azzahra; Mahimma Romadhona; Sri Wulandari (VISA: Journal of Vision and Ideas, 2026)
Introducing astronomy at an early age can help foster children’s interest in and understanding of science in the future. However, astronomy material is often considered complex and abstract. Deaf children have heard impairments and a limited vocabulary, making it difficult for them to comprehend lengthy texts. Video media, while accessible, is not entirely suitable for deaf children because it is passive and moves too quickly, even when subtitles are available. Therefore, more visual and interactive reading materials are needed to support deaf children in processing the content of the text. This study aims to design a character for an Augmented Reality-based illustrated book on astronomy for deaf children. The method used is qualitative, employing the design thinking approach with the stages of empathize, define, ideate, prototype, and test. Data collection techniques included observations in bookstores, interviews with experts, focus group discussions with deaf children, and a literature review. The result of this design is the character Keza, who is the main character in the Augmented Reality-based illustrated book. It is hoped that this design can help deaf children engage more closely with astronomy reading material in a visual and interactive way.